2018
DOI: 10.1080/02656736.2018.1438672
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical fractionation of tissues using microsecond-long HIFU pulses on a clinical MR-HIFU system

Abstract: Clinical MR-HIFU system was utilised to generate distinct types of lesions and to produce targeted thermomechanical bioeffects in ex vivo tissues. The results guide HIFU research on thermomechanical tissue bioeffects, inform future studies and advice sonication parameter selection for direct tumour ablation or immunomodulation using a clinical MR-HIFU system.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 28 publications
(16 citation statements)
references
References 57 publications
0
16
0
Order By: Relevance
“…The role of FUS in the tumor microenvironment remains to be elucidated for this study. FUS treatment, by itself or in combination with MBs, causes mechanical fractionation of the tumor tissues at the focal point and triggers the release of tumor antigens to the microenvironment [ 43 ]. Enhanced tumor antigen release potentiates dendritic cell maturation, which in turn triggers priming of the T cells and immunological responses against the tumor cells [ 44 , 45 ].…”
Section: Discussionmentioning
confidence: 99%
“…The role of FUS in the tumor microenvironment remains to be elucidated for this study. FUS treatment, by itself or in combination with MBs, causes mechanical fractionation of the tumor tissues at the focal point and triggers the release of tumor antigens to the microenvironment [ 43 ]. Enhanced tumor antigen release potentiates dendritic cell maturation, which in turn triggers priming of the T cells and immunological responses against the tumor cells [ 44 , 45 ].…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, we performed pulsed boiling histotripsy (BH) sonications using acoustic power of 450 W, 10 ms long pulses, and 30 pulses per trajectory point. BH is a HIFU technique that is capable of precise mechanical fractionation of target tissue with minimal surrounding heating [2, 3, 37]. Furthermore, as representative examples, HIFU sonications were performed in TMTCP embedded with either a rubber blood vessel -mimic with water flow, or plastic rib mimic (VeroWhitePlus, Stratasys, Ltd., MN, USA; acoustic attenuation = 3.0 dB/cm @ 1 MHz, speed of sound = 2539 m/s) [38].…”
Section: Methodsmentioning
confidence: 99%
“…High intensity focused ultrasound (HIFU) is a therapeutic modality useful for a wide variety of clinical applications, and is capable of non-invasive, volumetric tissue heating to induce targeted and localized thermal ablation, mild hyperthermia, and/or mechanical fractionation [1, 2, 3, 4]. HIFU is generally performed under magnetic resonance imaging (MR-HIFU) or ultrasound imaging (US-HIFU) guidance [5, 6, 7, 8, 9].…”
Section: Introductionmentioning
confidence: 99%
“…High-intensity focused ultrasound (HIFU) is a non-invasive therapy that is used in the clinic to thermally ablate solid tumors with high spatial precision, 74 and to mechanically disrupt tumors. 75 HIFU-mediated tumor fractionation may cause ICD and increase inflammation 76 and potentially lead to immune sensitisation. 77 Eranki et al 78 recently demonstrated a combination of HIFU and ICI significantly enhanced systemic antitumor responses and cured the majority of mice with large, established unilateral and bilateral neuroblastoma tumors.…”
Section: Conventional Cancer Therapiesmentioning
confidence: 99%
“…These data provide a promising alternative to transform a 'cold' tumor into a 'hot' one. High‐intensity focused ultrasound (HIFU) is a non‐invasive therapy that is used in the clinic to thermally ablate solid tumors with high spatial precision, 74 and to mechanically disrupt tumors 75 . HIFU‐mediated tumor fractionation may cause ICD and increase inflammation 76 and potentially lead to immune sensitisation 77 .…”
Section: Inducing Immunogenic Tumor Cell Death (Icd)mentioning
confidence: 99%